Quality of life, functional impairment and continuous performance task event‐related potentials (ERPs) in young adults with ADHD and autism: A twin study. Issue 3 (10th July 2022) - Aydin, Ümit; Capp, Simone J.; Tye, Charlotte; Colvert, Emma; Lau‐Zhu, Alex; Rijsdijk, Frühling; Palmer, Jason; McLoughlin, Gráinne
Abstract: Background: Young adulthood is a key developmental period for understanding outcomes of childhood onset attention‐deficit/hyperactivity disorder (ADHD) and autism. Measurement of functional impairment and quality of life (QoL) can provide important information on the real‐life challenges associated with these conditions. Event‐related potential (ERP) measures from the continuous performance task (CPT) have long been identified as altered in ADHD and autism but the role of these functions in the aetiological pathway to the disorders and associated impact on quality of life in young adulthood is unknown. Method: We investigated the relationships between ADHD and autism, functional impairment, quality of life, and ERP measures from the cued CPT (CPT‐OX) in a young adult twin sample (566 participants aged 22.43 ± 0.96 years old). Results: We observed significant phenotypic correlations between ADHD/autism and lower quality of life with specific genetic overlap between ADHD and physical health, psychological, and environmental aspects. We found significant phenotypic and genetic correlations between ADHD and functional impairment in all domains, as well as between autism and impairment in social functioning and lower impairment in risk‐taking. Both ADHD and autism were associated with attenuated amplitude of inhibitory and proactive control ERPs, with large genetic contributions to the overlap. We also found significant phenotypic correlations between these ERP measures and Weiss Functional Impairment Rating Scale (WFIRS) and QoL. Conclusion: This is the first study to investigate the phenotypic and genetic relationships between ADHD and autism, functional impairment, quality of life and ERP measures in young adulthood. Our findings could represent a step towards identifying ERP measures that are related to behaviour in the absence of overt symptoms. Abstract : Young adulthood (ages 18–25) is a key developmental period for understanding adult outcomes of childhood onset ADHD and autism. We investigated the relationships between ADHD and autism, functional impairment, quality of life, and event‐related potentials from continuous performance task in a young adult twin sample. We observed significant associations accompanied with significant genetic and environmental overlaps in many cases.